Applied nanotechnology for quantum mechanics - Berry, Helan (New Delhi: Amiga Press, 2021)
Mechanics is the branch of physics dealing with the effects of forces on the motions of bodies. In what is known as the classical picture, the world is composed of distinct elements, each possessing a definite position and velocity. As we get better at controlling materials and fabricating devices on the atomic scale, we'll need more "quantum engineers" to tackle the inherent challenges of technologies that exploit quantum effects. Although many modern devices rely on quantum mechanics in one way or another-for example, on population inversion in lasers or electron tunneling in transistors-most of those quantum effects can be described semi classically and are accessible to engineers who have taken the standard courses on solid-state devices. The Boltzmann distribution often causes confusion. People who are used to the principle of equal a priori probabilities, which says that all microstates are equally probable, are understandably surprised when they come across the Boltzmann distribution which says that high energy microstates are markedly less probable then low energy states.
Includes Bibliography and index
Keywords: Quantum Mechanics -- Nanotechnology -- Boltzmann Distributions -- Black Body Radiation; Schrodinger Wave Equation and Mechanics